2018
DOI: 10.1002/jhet.3174
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Some Novel Thiazolo[3,2‐a]pyrimidine and Pyrimido[2,1‐b][1,3]thiazine Derivatives and their Antimicrobial Evaluation

Abstract: A 2‐(2‐Mercapto‐4‐(4‐phenoxyphenyl)‐6‐(thiophen‐2‐yl)‐1,6‐dihydropyrimidin‐5‐yl) acetic acid was used as a reactive key precursor to design various pyrimidine derivatives such as thiazolo[3,2‐a]pyrimidines and pyrimido[2,1‐b][1,3]thiazines. The chemical structures of the newly synthesized products were confirmed by their elemental analyses and spectral data (IR, 1H NMR, 13C NMR, and mass spectra). The antibacterial and antifungal activities of some of the synthesized products were also evaluated, and it was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…(Table 3) Tetrazolopyrimidine attached to the pyrazole was a new structural type that could increase antibacterial activity. Besides, Behalo et al [42] prepared several novel thiazolo [3,2a]pyrimidines with potent activity against Streptococcus sp., B. subtilis, E. coli, A. niger and C. albicans compared to reference streptomycin and ketoconazole, which indicated that pyrimidine derivatives with thiazole or isoxazole moiety (compounds 69 and 70) ( Figure 12) were essential for enhancing antimicrobial activity.…”
Section: Other Ortho-condensed Bicycles Containing Pyrimidinementioning
confidence: 99%
“…(Table 3) Tetrazolopyrimidine attached to the pyrazole was a new structural type that could increase antibacterial activity. Besides, Behalo et al [42] prepared several novel thiazolo [3,2a]pyrimidines with potent activity against Streptococcus sp., B. subtilis, E. coli, A. niger and C. albicans compared to reference streptomycin and ketoconazole, which indicated that pyrimidine derivatives with thiazole or isoxazole moiety (compounds 69 and 70) ( Figure 12) were essential for enhancing antimicrobial activity.…”
Section: Other Ortho-condensed Bicycles Containing Pyrimidinementioning
confidence: 99%
“…In addition ,is othiocyanates are a class of organic compounds with well-known potent pharmaceutical applications [18,19] and are very popular in drug discovery [20][21][22] On the basis of these experiences and in continuation of our ongoing interest in the design of bioactive heterocyclic molecules [23][24][25][26][27], the present work involves a facilesynthesis of a series of five and six-membered heterocyclic compounds as triazole, quinazoline, thiazolidine and oxazine derivatives using 2-(4-phenoxybenzoyl)benzoyl is othiocyanate(2).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pyrimidine derivatives are an important group of heterocyclic compounds that possess wide range of pharmacological properties, which include their uses as antimicrobial [17][18][19][20], anticancer [21][22][23][24][25], antitumor [26], antioxidant [27], anti-inflammatory [28] and antiviral [29].In view of these observations and in continuation to our ongoing interest in the design of bio-active heterocyclic molecules [30][31][32][33][34][35], the present work involves synthesis of chalcone derivatives using choline chloride-urea mixture as a deep eutectic solvent and construct a series of new heterocyclic molecules that have remarkable biological activities.…”
Section: Introductionmentioning
confidence: 99%